(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
This research attempts to determine the survival rate and identify the risk factors affecting the survival of breast cancer patients. The study used 334 breast cancer patients from University College Hospital (UCH), Ibadan. The Kaplan-Meier estimator result shows that 70 patients survived after treatment, the median survival age is 58 years old and the median survival time is 1423 days which is equivalent to 4 years with survival probability of 0.455. Three survival models namely; Cox proportional, Weibull and Log-logistic regression models were fitted to the data. Cox proportional model has the lowest value of Akaike Information Criterion (AIC) (724.6865) and Bayesian Information Criterion (BIC) (745.1765) is considered the best fitted model. The result of Cox proportional model shows that the prognostic factors affecting the risk of dying from breast cancer are Histology (MC), Tumor stage II, Surgical type (MRM) and Surgical type (SM).